Thermoanalytical and spectroscopic characteristics of young and old leaves powder and methanolic extracts of Niedenzuella multiglandulosa - Russo, Helena Mannochio [UNESP]; Nunes, Wilhan Donizete Gonçalves [UNESP]; da Silva Bolzani, Vanderlan [UNESP]; Ionashiro, Massao [UNESP]; Caires, Flávio Junior [UNESP] (Springer Nature, 2018)
Niedenzuella multiglandulosa is a plant species known for having high toxicity and to cause death in cattle and sheep, promoting economic losses in Brazilian trade balance difficult to estimate. This work aims to evaluate the potential of thermoanalytical techniques (TG–DSC, TG-FTIR) and FTIR to identify compositional differences between the powder samples and methanolic extracts of young and old leaves. The TG–DSC profile for young and old leaves powder and extract presented some differences, mainly in the fourth mass loss step, that was attributed to the greater content of tannins in old leaves as also evidenced by FTIR. The cyclic DSC and TG curves showed that the leaves samples are highly hygroscopic, adsorbing water vapor even from the controlled humidity atmosphere. This characteristic thermal behavior can be useful for sample identification and characterization.
Keywords: Evolved gas analysis; Natural products; Niedenzuella multiglandulosa; Thermal analysis